Fear of Missing Out (FOMO) in Generation Z Digital Investment: Risk Analysis and Islamic Finance Perspective - Ayu Cahya; Muzalifah (Jurnal Hadratul Madaniyah, 2026)
The rapid development of financial technology has significantly increased Generation Z’s participation in digital investment activities. However, limited attention has been given to the psychological factors influencing their investment decisions, particularly Fear of Missing Out (FOMO). This trend is supported by the accessibility of digital platforms and the widespread use of social media, which facilitate the dissemination of investment information. This study aims to analyze the influence of FOMO on digital investment behavior among Generation Z and to examine the phenomenon from the perspective of Islamic finance. This research employs a qualitative descriptive approach, with data collected through open-ended questionnaires distributed to 60 respondents who actively engage in digital investment. The data were analyzed using thematic analysis. The results indicate that FOMO significantly influences investment behavior by encouraging impulsive decisions driven by social media trends, with many respondents prioritizing short-term gains without sufficient risk analysis. From the perspective of Islamic finance, such behavior may lead to elements of gharar and maysir, which are not in accordance with Islamic financial principles. Therefore, improving financial literacy and Islamic financial literacy is essential to support more rational and responsible investment decisions.